Technical Efficiency Analysis of Scallion Farming (Case in Sumberejo Village, Batu District, Batu City) - Hana' Salsabila (Socio-Economics/Agribusiness Department, 2018)
Abstract: The objectives of this study are to: (1) analyze the scallion’s production input affecting output; (2) analyze technical efficiency rate of scallion farming, and (3) analyze the determinant factors of the scallion farming’s technical inefficiency. Research’s sample was selected using simple random sampling, as many as 56 farmers. Data analysis technique for the objectives are: (1) stochastic frontier analysis (SFA) using parameter estimation of Cobb-Douglas production function and (2) Tobit regression which all of that analysis techniques used STATA 14 software. The result of this study shows that only seeds and fertilizers (ZA and NPK) has significant influence on the scallion production. Overall, the respondents have not been achieved technical efficiency. Social economic factors such as the number of family member, the number of unemployed family member, farming experience, and credit access are have significant influence on the rate of scallion inefficiency.